In-vitro methods for testing dermal absorption and penetration of toxic gases. (January 2014) - Gaskin, Sharyn; Pisaniello, Dino; Edwards, John W.; Bromwich, David; Reed, Sue; Logan, Michael; Baxter, Christina
Abstract This technical note provides details of an experimental technique for in-vitro skin studies with atmospheric chemical challenge. There appear to be major evidence gaps in relation to dermal exposure of gases. We describe a modification of standard OECD protocols for an atmospheric delivery system which can be used to understand interaction of toxic gases and the skin. The system can be used to examine the mechanisms by which skin uptake occurs. Auxiliary components which allow for parameter variation such as temperature and relative humidity are also described. Methodology presented in this technical note uses examples of gas challenges (ammonia, chlorine) to illustrate its application to gases of differing physicochemical properties. This adapted protocol can be applied in the context of HAZMAT scenarios involving atmospheric toxic chemical release and dermal absorption potential under variable exposure conditions.